PELATIHAN TUTOR SEBAGAI AGEN DISEMINASI SENAM KREASI UNILA BE STRONG BAGI MAHASISWA - Goesthy Ayu Mariana Devi Lestari Goesthy Ayu; Dwiyana Habsary; Lora Gustia Ningsih; Susi Wendhaningsih; Agung Kurniawan (Education, Language, and Arts: Jurnal Pengabdian Kepada Masyarakat, 2026)
The low participation of academics in structured physical activity is a real challenge within the University of Lampung environment. The widespread sedentary lifestyle among students and education staff has a negative impact on health and productivity. As a response to this problem, an innovation resulting from research has been developed in the form of a Moderate version of the Unila Be Strong Creative Gymnastics, which is designed to be fun, dynamic and in line with physical activity needs in the campus environment. However, this exercise is not yet widespread because there are no internal tutors who are able to facilitate its implementation on a regular basis. This service activity aims to prepare students as gymnastics tutors who act as dissemination agents in work units, faculties and the campus community. Training includes mastery of basic gymnastic movements, group leadership skills, as well as a participatory facilitation approach. The output of the activity is increasing the competence of tutors, training modules, and the formation of a network of gymnastics practitioners within the University of Lampung. This activity is expected to be able to encourage the formation of a culture of healthy and active living, as well as strengthen the integration of research results in service to the campus community.   Rendahnya partisipasi akademisi dalam aktivitas fisik terstruktur merupakan tantangan nyata di lingkungan Universitas Lampung. Gaya hidup sedentari yang meluas di kalangan mahasiswa dan staf pengajar berdampak negatif pada kesehatan dan produktivitas. Sebagai respons terhadap masalah ini, sebuah inovasi hasil penelitian telah dikembangkan dalam bentuk versi Moderat dari Senam Kreatif Unila Be Strong, yang dirancang agar menyenangkan, dinamis, dan sesuai dengan kebutuhan aktivitas fisik di lingkungan kampus. Namun, latihan ini belum tersebar luas karena belum ada tutor internal yang mampu memfasilitasi pelaksanaannya secara teratur. Kegiatan pengabdian masyarakat ini bertujuan untuk mempersiapkan mahasiswa sebagai tutor senam yang bertindak sebagai agen penyebarluasan di unit kerja, fakultas, dan komunitas kampus. Pelatihan meliputi penguasaan gerakan senam dasar, keterampilan kepemimpinan kelompok, serta pendekatan fasilitasi partisipatif. Hasil dari kegiatan ini adalah peningkatan kompetensi tutor, modul pelatihan, dan pembentukan jaringan praktisi senam di Universitas Lampung. Kegiatan ini diharapkan dapat mendorong terbentuknya budaya hidup sehat dan aktif, serta memperkuat integrasi hasil penelitian dalam pelayanan kepada komunitas kampus.